ANALISIS PRODUKTIVITAS PRIMER PERAIRAN PANTAI AMAL KOTA TARAKAN BAGI PENGEMBANGAN BUDIDAYA RUMPUT LAUT - cahyadi, jimmy (Jurnal Harpodon Borneo, 2017)
Many factors to the effect of water productivity content like physical, chemical and biological. The basic of water productivity is how to make synthesis inorganic material to organic or photosynthesis process. Processed can make happen because of chlorophyll on algae especially phytoplanktons. The purpose of this research was to analyse primary productivity Amal water Tarakan city of North Borneo to sea weed development in 2016. The basic information can make manage it to continued seaweed aquaculture. The research methods were used GIS integration with ecology analyse in-situ and ek-situ combination. The research and analyse showed physical and chemical water still good average for seaweed live. The analyse chlorophyll a and primary productivity was moderate for seaweed aquaculture development. Key Words: Primary Productivity, Seaweed Aquaculture, Tarakan